The Sematico - Paradigmatic Structure of Phraseological Units in the Work” Qutadgu Bilig" - Abdullayeva Vazira Quronovna, (International Journal of Scientific Trends, 2024)
To date, a number of scientific studies have been carried out on the application of phraseological units in the text of a work of art not only in world but also in Uzbek linguistics, on the structure of phraseological units in it. This article reflects on the semantic-pragmatic structure of phraseological units in one of the Uzbek historical works, “Qutadgu bilig”.